Association of BK viremia with human leukocyte antigen mismatches and acute rejection, but not with type of calcineurin inhibitor. Issue 1 (18th October 2013) - Hässig, A.; Roos, M.; Etter, A.; Bossart, W.; Müller, N.; Schiesser, M.; Wüthrich, R.P.; Fehr, T.
Abstract Introduction BK viremia and polyomavirus‐associated nephropathy (PVN) represent a significant problem after kidney transplantation. Both are associated with intensified immunosuppression, but other risk factors and the impact of a screening program on outcome are incompletely understood. Methods Here, we report on the short‐ and long‐term outcome of a cohort of patients, who were transplanted in 2006/2007 and included in a newly introduced systematic 3‐monthly screening for BK viremia at the University Hospital Zurich. In patients testing positive for BK viremia, screening frequency was intensified and immunosuppression reduced. Patients with suspected PVN underwent transplant biopsy. Results Among 152 included patients, 49 (32%) tested positive for BK viremia, but only 8 developed biopsy‐proven PVN. BK viremia had a significant impact on estimated glomerular filtration rate and proteinuria in the first 2 years. Acute rejection episodes and the number of human leukocyte antigen (HLA) mismatches were the strongest independent predictors of BK viremia in a multiple logistic model. In contrast, no particular immunosuppressive agent or regimen was associated with enhanced risk. Conclusion Taken together, systematic BK viremia screening led to detection of a high percentage of viremic patients. With adjustment of immunosuppression, an excellent outcome was achieved. The independent association of HLA mismatches with BK viremia suggests impaired polyomavirus immunosurveillance in highly mismatched allografts.